ALOPECIA AREATA TREATED WITH HOMOEOPATHY - A CASE REPORT FROM “A STUDY TO EVALUATE THE EFFICACY OF PIX LIQUIDA FOR INDIVIDUALS SUFFERING FROM ALOPECIA AREATA” (CAHIERS MAGELLANES-NS, 2024)
Alopecia areata (AA) is one of the common form of a non-scarring alopecia. The most frequently appearing form is a little annular or spotty bald lesion generally on the scalp. Loss of immunological privilege is considered as the main etiology behind Alopecia Areata. A Female patient aged 21 years consulted for Alopecia Areata. Patient treated with homoeopathic medicine Pix Liquida. Severity of Alopecia areata assessed with the Severity of Alopecia Tool (SALT) score. Patient recovered after the Homoeopathic treatment administered. The severity of Alopecia tool (SALT) was developed as a standardized method for the measurement of scalp hair loss.